Surface Chemistry and Humidity in Powder Electrostatics: A Comparative Study between Tribocharging and Corona Discharge - Biegaj,KW; Rowland,MG; Lukas,TM; Heng,JYY (ACS Omega, 2017)
In the present study, the correlation between surface chemical groups and the electrostatic properties of particulate materials was studied. Glass beads were modified to produce OH-, NH2-, CN-, and F-functionalized materials. The materials were charged separately both by friction and by conventional corona charging, and the results were compared. The results obtained from both methods indicated that the electrostatic properties are directly related to the surface functional group chemistry, with hydrophobic groups accumulating greater quantities of charge than hydrophilic groups. The fluorine-rich surface accumulated 5.89 times greater charge upon tribocharging with stainless steel than the hydroxyl-rich surface. However, in contrast to the tribocharging method, the charge polarity could not be determined when corona charging was used. Moreover, discharge profiles at different humidity levels (25% RH, 50% RH, and 75% RH) were obtained for each modified surface, which showed that higher humidity facilitates faster charge decay; however, this enhancement is surface chemistry-dependent. By increasing the humidity from 25% RH to 75% RH, the charge relaxation times can be accelerated 1.6 times for fluorine and 12.2 times for the cyano group. These data confirm that surface functional groups may dictate powder electrostatic behavior and account for observed charge accumulation and discharge phenomena.